PENGARUH VISUAL MERCHANDISING, DISPLAY PRODUCT, DAN STORE ATMOSPHERE TERHADAP PERILAKU IMPULSE BUYING (STUDI KASUS : KONSUMEN MATAHARI DEPARTMENT STORE DI KOTA MAKASSAR) - Ismah Mutiah; Dian Parawansa; Abdul Razak Munir (Master of Management, Faculty of Economics and Business, Hasanuddin University., 2018)
This study purposed to determine the effect of visual merchandising, display product, and store atmosphere on impulsive behavior of consumers Matahari Department Store in Makassar City. Data used in this study were obtained from the questionnaire distribution. The number of samples used are 92 students of the Faculty of Economics and Business Hasanuddin University. The method of analysis used is multiple regression analysis method with hypothesis testing that is F test (simultan) and t test (partial). The results of this study indicate that variables visual merchandising, display product, and store atmosphere simultaneously have a positive and significant effect on consumer impulse buying variable Matahari Department Store in Makassar. While the most influential or dominant variable to consumer impulse buying variable Matahari Department Store in Makassar City is variable display product.